Factors related to implementation of an interprofessional communication concept in thoracic oncology: a mixed-methods study - Krug, Katja; Bossert, Jasmin; Möllinger, Sophia; Deis, Nicole; Unsöld, Laura; Siegle, Anja; Villalobos Bollen, Matthias Americo; Hagelskamp, Laura; Jung, Corinna; Thomas, Michael; Wensing, Michel (BMC palliative care, 2022)
An innovative patient-centred interprofessional communication concept with advanced lung cancer patients (Heidelberg Milestone Communication Approach, MCA) has been developed and implemented. Role changes and interprofessional communication are challenging in a busy outpatient oncology service. The aim of the study was to present attitudes to interprofessional collaboration of professions in thoracic oncology during the implementation of MCA and to explore factors and experiences healthcare team members associate with its implementation.